HUBUNGAN AKTIFITAS FISIK DENGAN KUALITAS TIDUR PADA LANSIA DI POSYANDU LANSIA DUSUN CANGKRING DESA KEDUNGLOSARI KECAMATAN TEMBALANG KABUPATEN JOMBANG: Aktifitas Fisik dengan Kualitas Tidur Lansia - Sholikhah, Dwi Uswatun; Sasmito, Nanang Bagus; Vidhiastutik, Yusiana; Wadid, Moh. Tri Widya (PRIMA WIYATA HEALTH, 2022)
Increasing age of elderly people can increase the level of health problems that arise in the form of changes in physical functional abilities, changes in body systems, changes in hormone levels, psychological changes that can cause changes in sleep quality. The purpose of this study was to determine the relationship between physical activity and sleep quality in the elderly. Design This research was correlational analytic with cross sectional design approach. The population of all patients in the Elderly Posyandu, Cangkring Subdistrict, Kedung Losari Village, Tembalang District, Jombang Regency, as many as 216 elderly. Purposive sampling technique. Respondents in this study were 54 respondents. The variables in this study were physical activity as the independent variable, and sleep quality as the dependent variable. Collecting data used a International Physical Activity Quesionnaire (IPAQ) and Pittsburgh Sleep Quality Index (PSQI). Data analysis used chi square. The results showed that most of the respondents had moderate physical activity as many as 35 respondents (64.8%) and most of the respondents had good sleep quality as many as 37 respondents (68.5%). The results of data analysis used the chi square test obtained the results of sig (2-tailed) p-value: 0.000 and error level (a): 0.05, so p<a so H0 was rejected and H1 was accepted, meaned that there was a relationship between physical activity and sleep quality. Regular physical activity is beneficial for improving sleep quality and getting positive health benefits. Lack of daily activities or unstructured activities will affect sleep time or sleep quality